Pulmonary function and concentrations of alpha 1-antitrypsin and immunoglobulin E in workers exposed to pancreatic enzymes. - Sjogren, B.; Hedenstierna, G. (Scandinavian Journal of Work, Environment & Health, 1983)
Fourteen workers exposed to pancreatic enzymes in tanneries were studied by interview, spirometry, and the single-breath nitrogen washout technique. Blood concentrations of alpha 1-antitrypsin and immunoglobulin E (IgE) were determined. For each exposed subject a nonexposed referent was selected, matched by sex, age, height and smoking habits. Symptoms in the airways were reported by four of the 14 subjects when weighing pancreatic enzymes. The exposed group did not show any deterioration in pulmonary volumes, forced expiratory flow, airway closure, or gas distribution when compared to the referents. The exposed group had significantly higher plasma levels of alpha 1-antitrypsin than the referents. This elevation might be a compensatory response to increased levels of proteases within the lungs. The serum levels of IgE did not differ between the groups.